(untitled) (diségno, 2021)
The aim of this article is to analyse the visual motifs proposed by the illustrations of Gustave Doré, a well-known French illustrator of the 19th century, by making a twofold comparison: on the one hand with the previous iconography from which he broke away, and on the other hand with the subsequent interpretations, particularly in the field of cinema, which decreed the definitive imposition of his visions in the collective imagination. In particular, the analysis focuses on the illustration of Dante’s Divine Comedy, of which Doré proposed a new interpretation, which takes the form of a powerful visual narrative with a strong scenic component. The changes with respect to Dante’s traditional iconography concern many aspects: from the features of the characters to the description of the environments, but above all a different perspective with which the illustrations are constructed to create a visual path that gives life to a dynamic setting of the narration in the modern sense.